HEALTH ISSUES AND SERVICES FOR CHILDREN IN INTERNALLY DISPLACED PERSONS CAMP IN BENIN CITY, EDO STATE - Omorogiuwa, Tracy B.E.; Oviahon, Kate Okuns (African Journal of Social and Behavioural Sciences, 2024)
This study examined the health issues and services for an internally displaced persons (IDPs) camp in Benin City. The challenges faced by the IDPs and by the various government agencies and NGOs involved in responding to their needs are also assessed, documented, compared, and analysed. This study adopted an exploratory research method to gather data on the impact and interrelationships of social and psychological variables in the Uhogua IDPs Centre in Benin City, Nigeria. This qualitative study employed the purposive sampling method to select 10 participants who were suitable for the study. The participants consisted of both male and female IDP camp administrators with at least 4 years of working experience in the camp. The research instrument used was an unstructured interview guide, and the data were verified using the member checking method. The data gathered were presented, transcribed, and analysed via manual content analysis. The results revealed that the inaccessibility of health care facilities has adverse effects on the health of children in IDP camps. Insufficient awareness of professionals of social welfare interventions also hinders support for IDPs or agencies from fully delivering needed services to IDPs. This study recommends the provision of primary healthcare facilities and personnel residents in camps and that the government establish a well-structured legal framework that could positively influence healthcare services for children in IDP camps.